PENDIDIKAN NASIONAL PARIWISATA TERHADAP PENGEMBANGAN DAN TANTANGAN DUNIA PARIWISATA (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2014)
Tourism development should be supported by qualified human resources, so that the development can be carried out on an ongoing basis and in accordance with the needs of the community. Improving the quality of eduaction is a matter that is not negotiable so that we can competence with foreign graduates (developed countries) is to implement a management system that is both educational and professional. With KKNI reflect the learning outcomes obtined one can through: (1) educatin; (2) training; (3) work experience, and (4) self-learning, so that would change how I view someone's competence, which is no longer solely on the diploma but with a view to the agreed framework of national qualifications as the basis for the recognition of one's educational outcomes widely (formally, non-formal, in formal or self-taught) are accountable and transparent.Institutional arrangement can be done by implementing a quality system of higher education